Literatura e meio ambiente : uma abordagem ecopoética em Manoel de Barros - Correia, Fernanda Bezerra de Aragão (2019)
This thesis aims to deepen critical thinking about this evident and ancient relationship between literature and the environment, with an approach that is not unilateral, that is, an approach that is not strictly philosophical, sociological, literary or ecological, but, yes, interdisciplinary. To this end, we intend to study and broaden the debate on ecocriticism as a nuclear and articulating issue of this interdisciplinarity, so that it is possible to contribute and strengthen ecocritics studies within the Environmental Sciences. Our main argument is to substantiate how ecocriticism functions as an opening for an ecopoeticin the field of poetry. We will take, therefore, some poems of great relevance, by the Brazilian author Manoel de Barros, not in a way to make a literary analysis, but to argue how poetry themeizes and illustrates the relationship literature and environment through ecopoetics, dedemonstrating, thus, as this contributes both to literary studies and environmental sciences. Faced with the scenario in which the global environment is located, as well as movements for ecological conservation and preservation, to study the interrelationship of man-nature, in an ecocentric perspective, through ecocriticism, and taking the poems as a contribution, it will be of great relevance to help readers position themselves ecologically. Ecocriticism proposes an epistemological framework to take care of this interrelationship, since it is one of the theoretical approaches that covers literature, in this case poetry, with other disciplines, which highlights attention in the relations between nature and Literature. As a theoretical framework we will turn to the great scholars of ecocriticism internationally, such as The British Greg Garrard, the American Cherryl Glotfelty, whose work was the pioneer and canonical on the subject, the Spanish Carmen Flys-Junquera, among others. And thus, the environmental problem ceases to be a subject that science can only solve, since it involves cultural issues, making fundamental the contribution of humanities. The interest of a theoretical deepening of ecocriticism in another field of study will be fundamental not only by seeking to solve a critical gap, but also with regard to poetic corpus, because the said critical current, taken as a guiding thread, will enable the foundation and consolidation of ecopoetics that articulatephilosophy and literature, seeking, certainly, to problematize the limits and boundaries between the philosophical (philosophy of nature) and literary (ecocriticism) fields, as well as the concept of nature, arguing that manoel de Barros's poems are a primordial ground for understanding nature, not only as a space of contemplation (Plotino), or a place where man walks, dominates and reads nature (Bacon), but as a sum of discourses, which can contribute directly to environmental awareness.